2020
DOI: 10.1111/ppc.12550
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sociodemographic characteristics of university students on emotional eating behavior

Abstract: Purpose: This descriptive study was conducted for the purpose of determining the effect of sociodemographic characteristics of university students on emotional eating behavior. Design and Methods: The study was completed with a total of 537 students. A descriptive questionnaire and the Emotional Eating Scale were used. Descriptive statistics, correlation, and regression analyses were used. Finding: It was found that emotional eating was positively correlated with body mass index and weight. It was determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…Moreover, McCrone, Dennis, Tomoyasu, and Carroll 28 concluded that eating induced by negative mood and eating when not hungry in the face of emotional stimuli were more common amongst women. 28 Similarly, Işık and Cengiz 20 disclosed the fact that women with eating disorders responded to negative moods by binge-eating reactions in support of our findings. One may offer several reasons why emotional eating is more common among women than men.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Moreover, McCrone, Dennis, Tomoyasu, and Carroll 28 concluded that eating induced by negative mood and eating when not hungry in the face of emotional stimuli were more common amongst women. 28 Similarly, Işık and Cengiz 20 disclosed the fact that women with eating disorders responded to negative moods by binge-eating reactions in support of our findings. One may offer several reasons why emotional eating is more common among women than men.…”
Section: Discussionsupporting
confidence: 84%
“…36 In this context, being overweight can be a risk factor for emotional eating. 20,[37][38][39] This condition may emerge as a consequence of everlasting diet programs and restricted meal regimen, and dissatisfaction on the body/low selfesteem. In our study, it was found out that the overweight students exhibited a more despairing approach and a lesser optimistic approach compared to normal-weight students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that the eating behaviors of participants showing anger were significantly affected (24). Another relevant study reported that negative moods such as anger and boredom affected the emotional eating behaviors of the participants (25). One of the target groups of nurses who provide care and counseling to the public while in direct contact with the public is overweight and obese people (26).…”
Section: Discussionmentioning
confidence: 99%
“…Petroni et al found a significant relationship between dietary background, psychological/psychiatric problems and poor quality of life (23). Another relevant study revealed that variables such as will, anger, BMI and weight explained emotional eating behaviors (25). Moreover, another study in the relevant literature reported that people's perceptions toward body weight were directly related to their health and well-being (8) .…”
Section: Discussionmentioning
confidence: 99%